The effect of soy products with or without moist extrusion on starter pig performance - K G Friesen; J A Hansen; Jim L Nelssen; Robert D Goodband; Keith C Behnke (Kansas Agricultural Experiment Station Research Reports, 1991)
One hundred and seventy pigs, averaging 11.88 lb and 21 d of age, were utilized in a 35 d experiment evaluating the effect of moist extrusion of soy products on growth performance and nutrient digestibility. Pigs were fed one of seven experimental diets for the first 14 d of the trial. A diet containing all milk protein served as a control. Comparisons were made between pigs fed the milk control diet and diets containing either defatted soy flakes, soy protein concentrate, or experimental soy protein concentrate. Treatments consisted of: 1) 20% dried skim milk, 20% dried whey; 2 and 3) defatted soy flakes with or without moist extrusion; 4 and 5) soy protein concentrate with or without moist extrusion; 6 and 7) experimental soy protein concentrate with or without moist extrusion. A common diet formulated to 1.25% lysine was fed from d 14 to 35. Weekly pig weights and feed consumption were recorded to determine average daily gain (ADG), average daily feed intake (ADFI), and feed efficiency (F/G). Blood serum samples were collected on d 13 and analyzed for urea nitrogen concentration. Fecal samples were collected on d 14 to determine apparent dry matter (OM) and nitrogen (N) digestibilities. A significant interaction between extrusion and protein source was detected in ADG and F/G during the first 2 wk post-weaning. Pigs fed soy proteins processed by moist extrusion had improved ADG and FfG, with the largest improvement being detected in defatted soy flakes. Dry matter and N digestibilities were increased by processing soy proteins with moist 1 Department of Grain Science. extrusion. Nitrogen utilization was also improved by utilizing moist extrusion as evidenced by decreased concentrations of blood urea nitrogen. Based on these results, soy protein utilization in starter pig diets can be improved with moist extrusion. Though a large response to extrusion was not detected in highly processed soy products (soy protein concentrate and experimental soy protein concentrate), dramatic improvements in growth performance resulted when soy flakes were processed by moist extrusion.; Swine Day, Manhattan, KS, November 21. 1991
Keywords: Swine day; 1991; Kansas Agricultural Experiment Station contribution; no. 92-193-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 641; Swine; Soybean; Starter; Performance; Milk